Human Resource Outsourcing: Lesson from Multinational Enterprises - Halim, Hasliza Abdul; Ha, Norbani Che (Bina Nusantara University, 2011)
This paper examines the consequence of the organization internalization on the practice of human resource (HR) outsourcing among manufacturing organizations. The assumption is that HR outsourcing is perceived as an innovative practice and that multinational enterprise (MNEs) will employ this practice more than local organizations. The data was gathered from survey questionnaires of 232 manufacturing organizations. Of the sample, 113 organizations engaged with HR outsourcing, and 71 are MNEs that partially outsource their HR functions. The findings reveal that HR outsourcing among MNEs is used to a greater extent than local organizations. A significant difference is found in the extent of outsourcing payroll, benefits, training and recruitment between MNEs and in local organizations.